Effect of supplementation of feed additives alone and in combination on liver function test profile in crossbred lambs fed oats straw based complete diet - Yasir Afzal Beigh; Abdul Majeed Ganai; Haidar Ali Ahmad; Ishfaq Ahmad; Umar Amin; Masood Saleem Mir; Danish Masood (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was planned to assess the effect of feeding complete diet supplemented with exogenous fibrolytic enzymes cocktail and Artemisia absinthium L. herb alone and in combination as feed additives on liver function test profile in sheep. Twenty crossbred lambs randomly divided into four groups of 5 animals in each were offered complete diets based on oats straw- 40 parts, mixed grass hay- 20 parts and concentrate mixture- 40 parts for a period of 90 days. The complete feeds were supplemented either alone with exogenous fibrolytic enzymes cocktail (T 1 ) @ 6 g/kg DM and A. absinthium L. herb (T 2 ) @ 4.5% of DM or in combination (T 3 ) of the two, whereas the complete feed without any supplementation (T 0 ) served as control. Blood monitoring was carried out at the start and subsequently at monthly intervals of the experiment. Supplementation of feed additives had significant effect on overall mean serum globulin, A:G ratio (P<0.01) and ALT (P<0.05) levels. It is concluded that supplementation of exogenous fibrolytic enzymes cocktail and A. absinthium L. herb alone or in combination to complete diet is possible for intensive rearing of lambs without any adverse effect on liver functioning.